2014
DOI: 10.2298/jsc130512022p
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and high in vitro cytotoxicity of some (S,S)-ethylenediamine-N,N’-di-2-propanoate dihydrochloride esters

Abstract: A novel (S,S)-R 2 eddip ester, O,O′-diisopentyl-(S,S)-ethylenediamine--N,N′-di-2-propanoate dihydrochloride (1) was synthesized and characterized by IR, 1 H-and 13 C-NMR spectroscopy, mass spectroscopy and elemental analysis. In vitro antitumor action of 1, and two more R 2 eddip esters, dialkyl (S,S)-ethylenediamine-N,N′-di-2-propanoate dihydrochlorides, obtained before (alkyl = n-Bu or n-Pe, 2 and 3, respectively), was determined against cervix adenocarcinoma (HeLa), human melanoma (Fem-x), human chronic mye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…IC 50 values for the action of SFN and PEITC on Fem-x cells were similar. It should be emphasized that both values are similar to the IC 50 value of (5.51 ± 0.3 mmoL m -3 ) for the action of cisplatin on Fem-x cells that was reported by Pantelić et al 26 in the same experimental design. Even stronger an-tiproliferative potential of BITC on Fem-x cells compared to the action of cisplatin, with twice as lower IC 50 value was demonstrated in the present study.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…IC 50 values for the action of SFN and PEITC on Fem-x cells were similar. It should be emphasized that both values are similar to the IC 50 value of (5.51 ± 0.3 mmoL m -3 ) for the action of cisplatin on Fem-x cells that was reported by Pantelić et al 26 in the same experimental design. Even stronger an-tiproliferative potential of BITC on Fem-x cells compared to the action of cisplatin, with twice as lower IC 50 value was demonstrated in the present study.…”
Section: Resultssupporting
confidence: 86%
“…Additionally, cell models used for the selectivity assessment usually include normal cells of the same origin in addition to malignant cells 26 or PBMCs, as proposed in our work. Prioritisation of PBMCs as a model was rationalised by important role of PBMC subpopulations in the immuno-logical control of tumor growth 33 and a possibility to include mitogen stimulated cells as a model of normal cells in the highly proliferative state.…”
Section: Discussionmentioning
confidence: 99%
“…[6] In contrast to cisplatin, these complexes mostly cause rapid, caspase-independent, oxidative stressmediated, non-apoptotic cell death characterized by massive cytoplasmic vacuolization, cell membrane damage and the absence of protective autophagy. [7,8] Indeed, organic ligands themselves exert significant in vitro toxicity probably due to an incorporated ethylenediamine group, which is known for its positive contribution to the cytotoxicity effect. [9] Ethylenediamine-N,N′-di-3-propanoate (R 2 eddp)-type esters such as diisopentyl-, di-n-butyl-and di-n-pentyl-(S,S)-ethylenediamine-N,N′-di-2-propanoate show even higher cytotoxicity and better selectivity against cervix adenocarcinoma cell line (HeLa), human melanoma (Fem-x) and human chronic myelogenous leukaemia (K562) cells in comparison to cisplatin.…”
Section: Introductionmentioning
confidence: 99%
“…[9] Ethylenediamine-N,N′-di-3-propanoate (R 2 eddp)-type esters such as diisopentyl-, di-n-butyl-and di-n-pentyl-(S,S)-ethylenediamine-N,N′-di-2-propanoate show even higher cytotoxicity and better selectivity against cervix adenocarcinoma cell line (HeLa), human melanoma (Fem-x) and human chronic myelogenous leukaemia (K562) cells in comparison to cisplatin. [8] Studies on the new cyclohexyl-1,3-propanediamine-N,N′-diacetate molecules showed that esterification was required for the novel compounds' cytotoxic action. The n-butyl ester was more efficient in comparison to acid from the same group of ligands.…”
Section: Introductionmentioning
confidence: 99%